2010
DOI: 10.1093/her/cyq049
|View full text |Cite
|
Sign up to set email alerts
|

Process evaluation of HIV prevention peer groups in Malawi: a look inside the black box

Abstract: This paper reports the process evaluation of a peer group intervention for human immunodeficiency virus (HIV) prevention which had positive outcomes for three target groups in Malawi: rural adults, adolescents and urban hospital workers. The six-session intervention was delivered to small groups of 10-12 participants by 85 trained volunteer peer leaders working in pairs. A descriptive, observational mixed methods design was used with a convenience sample of 294 intervention sessions. Using project records and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…It was unclear who intervention deliverers were in 12 studies (21.8%) [26, 39, 46, 50, 51, 55, 5964], but in studies where this information was identifiable, deliverers were most frequently nurses (10 studies, 18.2%) [33, 3537, 40, 47, 52, 6567]. With regards to level and mode of delivery, interventions were most frequently delivered at the individual (25 studies, 45.5%) [2729, 33, 34, 40, 41, 45, 46, 48, 50–52, 54, 56, 60, 63, 65, 66, 6873] and group level (19 studies, 35.1%) [26, 31, 32, 38, 39, 42, 43, 49, 53, 55, 58, 61, 62, 64, 67, 7477]. Face to face was the most common (28 studies, 50.9%) mode of delivery [27, 29, 31, 32, 3538, 4145, 49, 50, 56, 58, 6062, 6668, 7478].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was unclear who intervention deliverers were in 12 studies (21.8%) [26, 39, 46, 50, 51, 55, 5964], but in studies where this information was identifiable, deliverers were most frequently nurses (10 studies, 18.2%) [33, 3537, 40, 47, 52, 6567]. With regards to level and mode of delivery, interventions were most frequently delivered at the individual (25 studies, 45.5%) [2729, 33, 34, 40, 41, 45, 46, 48, 50–52, 54, 56, 60, 63, 65, 66, 6873] and group level (19 studies, 35.1%) [26, 31, 32, 38, 39, 42, 43, 49, 53, 55, 58, 61, 62, 64, 67, 7477]. Face to face was the most common (28 studies, 50.9%) mode of delivery [27, 29, 31, 32, 3538, 4145, 49, 50, 56, 58, 6062, 6668, 7478].…”
Section: Resultsmentioning
confidence: 99%
“…none of the studies included from the electronic database search reported using the BCC framework). Other frameworks that informed the studies reviewed included the process evaluation framework by Linnan and Steckler (2002) [22] in 11 (20.0%) [27, 46, 52, 53, 55, 60, 66, 68, 69, 71, 74], Lichstein et al’s Treatment Implementation Model (TIM) [21] in 4 (7.3%) studies [28, 39, 40, 67], Saunders et al’s framework [23] in 5 (9.1%) studies [26, 30, 46, 49, 59], the Reach, Efficacy, Adoption, Implementation, and Maintenance (RE-AIM) framework [79] in 2 (3.6%) studies [46, 70], Dane & Schneider’s framework [80] in 2 (3.6%) studies [38, 76], Dusenbury et al’s framework [81, 82] in 2 (3.6%) studies [38, 62], Baranowski et al’s framework [83] in 1 (1.8%) study [52]. A brief definition of how receipt is defined in these frameworks is available in notes below the Table in Additional file 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations